Clinical Effectiveness of Home‐Based Telerehabilitation Program for Geriatric Hip Fracture Following Total Hip Replacement. Issue 2 (29th November 2022) - Wu, Wei‐yong; Zhang, Yin‐guang; Zhang, Yuan‐Yuan; Peng, Bing; Xu, Wei‐guo
Abstract : Objective: To compare the effectiveness of a six‐month home‐based telerehabilitation based on the Internet‐based rehabilitation management system coupled with conventional outpatient care in elderly patients with hip fractures following total hip replacement (THR). Methods: Elderly patients (aged over 65 years) with first hip fractures who underwent THR between March 2018 and September 2018 in Tianjin Hospital were enrolled in this study. Patients were divided into two groups: telerehabilitation group (n = 43) and telephone group (n = 42). A Internet‐based telerehabilitation management system was established and applied on patients in the telerehabilitation group. For patients in the telephone group, the rehabilitation intervention was administered through conventional outpatient care (telephone along with outpatient follow‐up). Data from the Harris hip scale (HHS), functional independence measure (FIM), self‐rating anxiety scale (SAS), and postoperative complications at 1, 3, and 6 months after surgery were collected and compared between the two groups. Results: A total of 85 elderly patients completed the 6‐month follow‐up assessment. Results showed that the HHS score was significantly higher in the telerehabilitation group than in the telephone group at 1 month (66.35 ± 4.63 vs 63.48 ± 4.49), 3 months (76.33 ± 4.52 vs 71.81 ± 3.84), and 6 months (84.23 ± 3.13 vs 77.29 ± 4.95) after surgery ( P  < 0.001). The FIM score was significantly higher in the telerehabilitation group than in the telephone group at 1 month (89.00 ± 5.63 vs 73.35 ± 8.70), 3 months (100.16 ± 4.56 vs 92.81 ± 5.17), and 6 months (111.70 ± 3.13 vs 98.64 ± 5.12) after surgery ( P  < 0.001). The SAS score was significantly lower in the telerehabilitation group than in the telephone group at 1 month (42.40 ± 3.07 vs 46.21 ± 3.53), 3 months (36.77 ± 2.26 vs 40.24 ± 1.66), and 6 months (29.26 ± 1.63 vs 33.81 ± 2.62) after surgery ( P  < 0.001). The overall complication rate was significantly lower in the telerehabilitation group than in the telephone group (14% vs 40.5%) ( P  < 0.05). Conclusion: Internet‐based rehabilitation management system can not only promote the physical rehabilitation of patients, but also play a positive role in psychological rehabilitation and the prevention of complications, which provides new ideas and methods for clinical rehabilitation. Abstract : A total of 103 potentially eligible older patients (aged over 65 years) treated at Tianjin Hospital after total hip replacement (THR) was identified, of which 85 participants were enrolled in the study and were allocated into the telerehabilitation (n = 43) or telephone groups (n = 42). The reasons for exclusion and dropouts of participants during the data collection and per‐protocol analysis are provided in the flow diagram (Fig. 1).